Towards Academic Medical Library Standards in India: A Call for Action - Narang, Sangeeta; Kumar Vishwakarma, Mahender (Journal of Information and Knowledge, 2021)
With the rapidly growing healthcare information, medical librarians’ roles and responsibilities in health care institutions are expanding, more so in the present context of Corona virus pandemic. Librarians in western countries are engaged in organizing, managing information resources, and offering seamless access to library materials to their users, supporting them with online consultation and research services. Medical libraries in India are slow to pick up the necessary momentum. They are underrepresented in medical education, their roles and responsibilities meagerly defined in institutions’ employment regulations and there is little in terms of medical library standards for India. Even the newly constituted National Medical Commission has not taken note of the role medical libraries can play going by its recently released ’Minimum Requirement for Annual MBBS Admissions Regulations 2020’. What should be minimum medical library standards, role of libraries in medical education in India? In order to answer these questions, the author reviewed: (i) higher education policy documents, inspection documents, UGC guidelines, and their coverage on libraries, (ii) standards developed by professional library associations, and (iii) publications on library standards in international journals. Medical education is a highly specialized area where serving librarians require a unique set of skills to meet the information needs of the diverse users of medical libraries. On reviewing these native documents, it was found that there is little content available for medical libraries to adopt in India. Therefore, to get a wider picture, library standards for higher education developed by professional library associations of the advanced countries were examined. Based on these, a model minimum standard for medical libraries in India is proposed. The right mix of resources, staff, funds, and infrastructure is important for the proper functioning of academic medical libraries in medical institutions. This will in turn enhance the quality of medical education, health care services, and research in the country.